Enriched Binary Increase Congestion Control Algorithms for Effective Data Transmission in Satellite Network - Nirmala, M.; Pujeri, Ramachandra V.; Valarmathi , M. L. (Research and Developments in Engineering Research Vol. 2, 2023)
In terms of wired and wireless media, satellite networking fundamentals are completely different. The TCP/IP protocol's performance on satellite networks is entirely different since it was not intended to operate effectively over high-latency or noisy channels. The influence of TCP on the effectiveness of satellite communications was studied. The behavior of TCP/IP will significantly vary from one satellite constellation to another. Both the Adaptive Window Increment based BIC TCP Algorithm (bic AWI) and Dynamic Parameter Estimation based Binary Increase Congestion control Algorithm (bic DPE) fared well for data transfer in satellite networks. There have been suggested changes made to bic-tcp, and under the Iridium satellite constellation, the performance of the enhanced protocols "bic AWI" and "bic DPE" has been compared with that of regular bic-tcp. The algorithms' performance was evaluated using appropriate measures, and the suggested bic DPE outperformed both the standard bic-tcp and our old "bic AWI" technique.